Mental disorders and lack of social support among refugees and Ugandan nationals screening for HIV at health centers in Nakivale refugee settlement in southwestern Uganda - Robin E. Klabbers; Scholastic Ashaba; Joshua Stern; Zikama Faustin; Alexander C. Tsai; Julius Kasozi; Andrew Kambugu; Peter Ventevogel; Ingrid V. Bassett; Kelli N. O'Laughlin (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Exposure to potentially traumatic events and daily stressors in humanitarian settings puts refugees and asylum seekers (henceforth collectively referred to as refugees) at increased risk for mental disorders. Little is known about how mental disorder prevalence compares between refugees and national populations who live in the same settings and are exposed to many of the same daily challenges. We aimed to compare the proportions of refugees and Ugandan nationals screening positive for mental disorders in a Ugandan refugee settlement to inform targeted health interventions. Given displacement's disruptive effect on social networks and the importance of social support for mental health, we also aimed to assess social support. # Methods Refugees and Ugandan nationals voluntarily testing for HIV at health centers in Nakivale Refugee Settlement were screened for post-traumatic stress disorder (PTSD CheckList-6 -- Civilian Version \[PCL-6\]), depression (Patient Health Questionnaire-9 \[PHQ-9\]), anxiety (General Anxiety Disorder-7 \[GAD-7\]), and lack of social support (Brief Social Support Scale \[BS6\]). The association between refugee versus Ugandan national status and the four outcomes was assessed using log-binomial regression. # Results Screening surveys were completed by 5,513 participants, including 3,622 refugees and 1,891 Ugandan nationals. A positive screen for PTSD, depression, anxiety and lack of social support was found for 2,388 (44%), 1,337 (25%), 1,241 (23%) and 631 (12%) participants, respectively. Refugee status was associated with a higher prevalence of a positive screen for PTSD (prevalence ratio (PR)=1.15; 95% confidence interval (CI)=1.08-1.23), depression (PR=1.22; 95% CI=1.11-1.36), anxiety (PR=1.28; 95% CI=1.14-1.42), and lack of social support (PR=1.50; 95% CI=1.27-1.78). When adjusted for the other outcomes, the higher prevalence of a positive screen for PTSD, anxiety and lack of social support for refugees remained statistically significant. # Conclusions Elevated symptoms of mental disorders are found among refugees and Ugandan nationals testing for HIV in Nakivale Refugee Settlement. The significant association between refugee status and PTSD, anxiety and lack of social support symptoms highlights the distinct needs of this population. To determine the prevalence of mental disorders in these populations, comprehensive assessment, including psychological and neuropsychological testing, is needed.